“Hongos micorrízicos arbusculares sobre el comportamiento agronómico y rendimiento del cultivo de arroz (Oryza sativa L.) bajo condiciones de Babahoyo” - Onofre Berrúz, Víctor Efraín (2019)
. SUMMARY The present experimental work was carried out in the lands owned by Mr. Alejandro Ramos Elizondo, in the Rcto. Bella Unión, located in the Pimicha parish of the Babahoyo canton, between the geographic coordinates UTM 656209,5 of South Latitude and 9795063.6 of West Longitude, with a height of 8 msmn. The area has a tropical climate, with an average annual temperature of 25.6 ° C, annual precipitation 1,730 mm, relative humidity of 82%. The soil is of alluvial origin, flat topography, clay loam texture, drainage and regular fertility. The rice seed variety Iniap "16" was used as genetic material. The treatments were constituted by the application of four products Micor 9 (dose of 1.0 L / ha), Glumix (20 kg / ha), Huxtable (3.0 kg / ha), Biofung (1.0 L / ha) more an absolute witness. The experimental design "Random blocks" with 5 treatments and 4 repetitions was used, the variables evaluated were subjected to the analysis of variance and to determine the statistical difference between the means of the treatments, the Tukey test was applied at 95% probability . All the tasks required for rice cultivation were carried out for normal development, such as land preparation, planting, fertilization, irrigation, weed control, insect and pest control and harvesting. Based on the results obtained, it was determined that arbuscular mycorrhizal fungi favored the development and nutrition of rice plants, variety Iniap "16"; the percentage of colonization, spore count and endophyte density was obtained by the treatment that Glumix was used in a dose of 20 kg / ha; the control treatment took time to flower; plant height, root and panicle length, number of tillers and panicles / m2, grains per panicles and weight of 1000 seeds stood out with the application of Glumix in a dose of 20 kg / ha and the highest yield of the crop with 4973, 8 kg / ha and net profit of $ 462.46 was recorded with the use of Glumix in a dose of 20 kg / ha. Keywords: rice, arbuscular mycorrhizal, yield.